Role of muscle relaxation in the correction of vestibulo-respiratory reactions in athletes - Tarabrina, N.Yu.; Wilczewski, Tomasz (Theory and Practice of Physical Culture, 2022)
The aim of the study was to study the possibility of using muscle relaxation as a means of correcting the negative influence of vestibular loads on the function of external respiration of wrestlers. For 81 athletes-wrestlers (men) (19.41±1.66 years), the parameters of the tone of paravertebral muscles (TPM) of the reflexogenic vascular zones of С3-Тh8 segments and the indices of spirometry at rest, after presentation of a vestibular load (Series-1), after the combined action of active traction rotational muscle relaxation (ATRM) and vestibular load (Series-2) were studied. It was shown that vestibular loads increase the tone of the cervical muscles in wrestlers by 4.72-11.54% (p<0.05). After the combined action of ATRM with vestibular loads, there was a significant decrease in myotonus at the VG15 point: up to 19.12% (p<0.001). In Series-2, the constants of the respiratory system significantly increased: vital lung capacity (VC) by 4.55% (p<0.01), maximum lung ventilation (MVV) by 6.55% (p<0.01) with a decrease in frequency respiration RR by 26.41% (p<0.001) and an increase in respiratory volume by 15.19% (p<0.01), which indicates an increase in the efficiency and effectiveness of breathing under conditions of vestibular loads. The method can be used in training process, sports medicine and physical rehabilitation.